Self-Esteem Among the Elderly in West Kalimantan - Indra Elisabet Lalangpuling; Kevin Giovani Pascoal; Sabrina Prisscilya Magdalena Pinontoan; Suwarja Suwarja; Meildy Esthevanus Pascoal (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Indonesia is a country that has an old population structure until 2020 it has increased to 10 percent of the total population. Changes due to ageing tend to cause health problems both physical health and mental health. Low self-esteem is a mental health problem that is prevalent in the elderly, so several factors are known to contribute to the decline in elderly self-esteem. The aim of this study was to determine the factors that influence the increase in self-esteem in the elderly. The design used was cross-sectional and the population of this study was elderly in PSTW X in West Kalimantan totalling 98 elderly with sampling. The results showed that the factors of gender and education. Meanwhile, other factors such as age, marital status, work history, reasons for entry and length of time at the institution did not contribute to increasing the self-esteem of the elderly. Based on the bivariate analysis with the chi-square test, there is a relationship between gender and education with self-esteem (p= 0.001, p= 0.000). It is hoped that this study can be carried out by providing interventions that can increase self-esteem in the elderly and reduce the long-term consequences of the elderly who experience low self-esteem.Negara Indonesia merupakan negara yang memiliki struktur penduduk tua hingga tahun 2020 telah meningkat menjadi 10 persen dari total penduduk. Perubahan akibat menua cenderung menyebabkan masalah kesehatan baik kesehatan fisik dan kesehatan mental. Harga diri rendah merupakan masalah kesehatan mental yang banyak dijumpai pada lansia sehingga beberapa faktor diketahui berkontribusi dalam menurunnya harga diri lansia. Tujuan studi ini untuk mengetahui faktor yang memengaruhi harga diri pada lansia. Rancangan penelitian yaitu desain cross-sectional dan populasi penelitian ini adalah lansia di PSTW X di Kalimantan Barat berjumlah 98 lansia dengan total sampling. Hasil penelitian didapatkan bahwa faktor jenis kelamin dan pendidikan. sementara itu, faktor lainnya seperti usia, status perkawinan, riwayat pekerjaan, alasan masuk serta lama dipanti tidak berkontribusi terhadap peningkatan harga diri lansia. Uji chi-square yang dilakukan menunjukan hubungan yang signifikan antara jenis kelamin dan pendidikan (p= 0,001, p-value = 0,000) dengan harga diri pada lanjut usia. Diharapkan fasilitas panti dapat menyediakan intervensi yang dapat meningkatkan harga diri pada lansia serta dampaki lain dari lansia yang mengalami harga diri rendah.